Rebiopsy in advanced non-small cell lung cancer, clinical relevance and prognostic implications. (June 2022) - Scheffler, Matthias; Wiesweg, Marcel; Michels, Sebastian; Nogová, Lucia; Kron, Anna; Herold, Thomas; Scheel, Andreas H.; Metzenmacher, Martin; Eberhardt, Wilfried E.; Reis, Henning; Fassunke, Jana; Darwiche, Kaid; et al.
Highlights: Rebiopsies of advanced NSCLC yield a high rate of clinically relevant findings. In tumors with EGFR/ALK/ROS1 alterations, rebiopsies lead to new findings in >50%. Clinical practice of rebiopsy selects a population with exceptional outcome. Abstract: Introduction: Rebiopsies of non-small cell lung cancers (NSCLC) are mainly performed to (i) cover the evolution of potentially amenable resistance mechanisms against a targeted therapy, and (ii) to identify new therapeutic targets which were not detected in the initial diagnostic biopsy. Comprehensive systematic analyses evaluating the value of rebiopsies are missing. Methods: Clinical databases from two large comprehensive cancer center networks were queried following prespecified criteria to identify prospectively entered NSCLC cases with at least one rebiopsy at disease progression. Clinicopathological and biomarker findings including multigene sequencing were correlated with clinical outcomes. Results: From a total of 17, 477 stage IV NSCLC patients, a cohort of 403 evaluable patients undergoing at least one rebiopsy of a primary tumor or metastasis was retrieved. Changes in biomarker profiles as compared to baseline were observed in 48.9%. In 31.3% of cases, findings of potential therapeutic relevance were revealed, including 18 patients (4.4%) with a targetable marker only detected at rebiopsy. New findings were more frequent (greater than50%) in NSCLC with EGFR/ALK/ROS1 alterations, including mutations of the dominant oncogene, TP53 mutations, and MET or ERBB2 amplifications. Patients undergoing rebiopsy exhibited superior overall survival compared to a control group, irrespective of presence (HR 0.28) or absence (HR 0.20, both p < 0.001) of a therapeutically targetable aberration. Conclusions: Rebiopsies at progression of advanced NSCLC are strongly supported by a high rate of clinically relevant findings. Current clinical practice selects a patient population with exceptional outcomes, which merits further characterization.